2022
DOI: 10.3390/biomedicines10030584
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Prediabetes and Non-Alcoholic Fatty Liver Disease Associated with Abdominal Obesity among Korean Children and Adolescents: Based on the Korea National Health and Nutrition Examination Survey between 2009 and 2018

Abstract: Investigations on the trends of prediabetes and non-alcoholic fatty liver disease (NAFLD) among children are scarce. We aimed to analyze the trends of prediabetes and NAFLD, as well as their association, among Korean children and adolescents from 2009 to 2018. This study investigated the prevalence of prediabetes, NAFLD, and abdominal obesity among 6327 children and adolescents aged 10–18 years according to age, sex, and body mass index (BMI) using a nationally representative survey. The prevalence of prediabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 43 publications
0
30
0
Order By: Relevance
“…In a population-based study from Korea, the prevalence of prediabetes was 15.6% among youth with NAFLD versus 7.8% among those without NAFLD. 1) In addition, the prevalence of NAFLD was 15.6% among youth with prediabetes versus 9.1% among those without prediabetes. The odds ratio of prediabetes for NAFLD was 1.85.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 96%
See 2 more Smart Citations
“…In a population-based study from Korea, the prevalence of prediabetes was 15.6% among youth with NAFLD versus 7.8% among those without NAFLD. 1) In addition, the prevalence of NAFLD was 15.6% among youth with prediabetes versus 9.1% among those without prediabetes. The odds ratio of prediabetes for NAFLD was 1.85.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 96%
“…19) In Korea, the prevalence of pediatric NAFLD, defined as an alanine aminotransferase (ALT) elevation without hepatitis B virus or hepatitis C virus infection, increased from 8.2% in 2009 to 12.1% in 2018 in a national surveillance study. 1) Moreover, the adverse trend was more prominent among youth, even young children, with a normal body mass index (BMI). In another Korean population-based study, the prevalence of NAFLD was 14.7% in boys and 6.5% in girls.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Strict connections between abdominal obesity and the incidence of prediabetes, T2D, hypertension, dyslipidemia, nonalcoholic fatty liver disease (NAFLD), and metabolic syndrome have been documented. [78][79][80] During the COVID-19 pandemic, a study of 432,302 children (ages 2-19 years) found that the rate of BMI increases nearly doubled compared to the pre-pandemic period. 22) This result, consistent with those of other studies, highlights the importance of obesity prevention and management strategies during and after the pandemic period.…”
Section: Covid-19 Obesity and T2dmentioning
confidence: 99%
“…The prevalence of NAFLD among youths increased from 19.34 million in 1990 to 29.49 million in 2017 according to the Global Burden of Disease database-based study, and corresponding values increased 2.7-fold from the 1980s to 2007–2010 in the USA [ 6 , 7 ]. In Korea, the prevalence of NAFLD increased from 8.17% in 2009 to 12.05% in 2018 among children and adolescents [ 8 ].…”
Section: Introductionmentioning
confidence: 99%